2006
DOI: 10.1007/s00125-006-0152-4
|View full text |Cite
|
Sign up to set email alerts
|

C-peptide exerts antithrombotic effects that are repressed by insulin in normal and diabetic mice

Abstract: Aims/hypothesis: Diabetic macro-and microangiopathy are associated with a high risk of vascular complications. The diabetic patient exhibits a pathological coagulation state, with an increased synthesis of coagulation factors and plasminogen activator inhibitor 1 (PAI-1) as well as an enhanced aggregation of platelets. Previous studies have shown that C-peptide can reduce leucocyteendothelial cell interaction and improve microvascular blood flow in patients with type 1 diabetes. In the present study, we examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 51 publications
1
13
0
1
Order By: Relevance
“…In contrast to this it has been revealed that C-peptide demonstrates antithrombotic effects in vivo . Administration of C-peptide in high doses caused delay in arteriolar and venular thrombus growth in normal and diabetic mice [43]. …”
Section: Proinflammatory In Vivo Effects Of C-peptidementioning
confidence: 99%
“…In contrast to this it has been revealed that C-peptide demonstrates antithrombotic effects in vivo . Administration of C-peptide in high doses caused delay in arteriolar and venular thrombus growth in normal and diabetic mice [43]. …”
Section: Proinflammatory In Vivo Effects Of C-peptidementioning
confidence: 99%
“…Both normal and diabetic animals showed a significant deceleration of microvascular thrombus formation after administration of high dose of C‐peptide. However, subsequent administration of insulin reversed this effect, suggesting that C‐peptide may not help the treatment and/or prevention of thrombosis when in combination with insulin . In contrast, it was demonstrated that C‐peptide or insulin alone inhibits low oxygen (O 2 )‐induced ATP release from healthy human erythrocytes.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, clinical trials in humans with T1DM and T2DM suggested beneficial impact of C‐peptide on kidney, retina, and nerve . High doses of C‐peptide were capable to reduce thrombus formation . It increases microvascular blood flow in the skin of T1DM patients, possibly by stimulating Na + , K + ‐ATPase activity and nitric oxide (NO) production .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such mechanisms were most likely mediated by a reduction in endothelial plasminogen activator inhibitor 1 (PAI-1) expression in arterioles and venules, but not by an effect on platelet activation. Interestingly, concomitant treatment with insulin abolished the effect of C-peptide on microvascular thrombus formation [21]. These data suggest that C-peptide could exhibit antithrombotic actions in vivo.…”
Section: C-peptide and Microvascular Thrombus Formation In Micementioning
confidence: 99%